Kadar Vitamin C dari Produk Propolis Geniotrigona Thoracica - Bagus Dadang Prasetiyo (NUCLEUS, 2023)
Propolis is a product of stingless bees that possesses adhesive properties and contains bioactive compounds with therapeutic effects. The flavonoid compounds found in propolis have a higher content compared to honey. In addition to flavonoids, propolis also contains minerals, vitamin C, and phenolic compounds. This research aims to examine the Vitamin C content of Geniotrigona Thoracica Propolis Products. Propolis extraction produced by Geniotrigona thoracic bees is employed in this study to obtain a comparison of vitamin C content under various treatments. The extraction method utilizes maceration and ultrasound-assisted techniques with ethanol and plant-based solvents. UV-Vis spectrophotometer analysis is conducted to determine the vitamin C content. The highest vitamin C content is obtained from the propolis extraction using the maceration method with ethanol solvent over 96 hours, resulting in a value of 8.9339 mg/100 g. Conversely, the lowest value stems from the treatment involving VCO extraction assisted by ultrasound for 30 minutes, yielding a value of 0.3062 mg/100 g. The greatest vitamin C content is achieved through the maceration extraction process using ethanol solvent, as compared to plant-based solvents.